2004
DOI: 10.1063/1.1767967
|View full text |Cite
|
Sign up to set email alerts
|

Direction-tunable cholesteric phase gratings

Abstract: In suitable conditions, the homeotropic aligned cholesteric liquid crystal (ChLC) cell can be in fingerprint texture when abruptly switching off the applied electric field. The stripe orientation depends not only on the thickness-to-pitch (d∕P0) ratio, but also on the applied driving voltage. In this paper, the ChLC phase grating with the field-controllable grating orientation is realized and the operational mechanism of this device is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The stripe direction of CLC gratings has also attracted the interest of researchers. [6][7][8] Yao et al proposed a direction-tunable CLC grating with homeotropic alignment and pattern electrode. 7 Nose et al also demonstrated voltage-dependent rotational diffraction gratings in hybrid aligned LC cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The stripe direction of CLC gratings has also attracted the interest of researchers. [6][7][8] Yao et al proposed a direction-tunable CLC grating with homeotropic alignment and pattern electrode. 7 Nose et al also demonstrated voltage-dependent rotational diffraction gratings in hybrid aligned LC cells.…”
mentioning
confidence: 99%
“…[6][7][8] Yao et al proposed a direction-tunable CLC grating with homeotropic alignment and pattern electrode. 7 Nose et al also demonstrated voltage-dependent rotational diffraction gratings in hybrid aligned LC cells. 8 However, because stripe direction was dependent on voltage, maintaining their direction was problematic when tuning the period by electric field.…”
mentioning
confidence: 99%
“…Here, they could achieve a large beam steering angle by continuous tuning of the pitch. Yao et al have demonstrated direction‐tunable, i.e., rotatable CLC gratings using patterned electrodes . In these gratings, the helical axis of the CLC rotates in the plane of the substrate and the rotation is controllable by the applied field.…”
Section: Control Of the Helical Axis Of Clcs By Different Stimulimentioning
confidence: 99%
“…As the results of orientation disorder of cholesteric fringes such as lying‐helix structures cannot be effectively used as a diffraction optical element. Nevertheless, there are methods to obtain an aligned fingerprint structures, which were used to create tunable DGs . In the paper, the authors used nematic 5CB doped with a mixture of nonphotochromic and photochromic chiral dopants 4 and 5, respectively (Figure b).…”
Section: Periodic Structures Spontaneously Forming In Clc Layersmentioning
confidence: 99%